The Economics of Population Ageing - John Stephenson; Grant Scobie (New Zealand Government, The Treasury, 2002)
Demographic forecasts predict that over the next fifty years the proportion of people in New Zealand over the age of 65 will more than double, from 12 percent in 1999 to 26 percent in 2050. This paper reviews potential economic implications of this demographic change in the following broad categories: Demographic change, Labour Markets, Fiscal Impacts, Capital Markets, and Long-run economic growth effects. A synopsis is made of the key economic and demographic issues relating to each category, and the paper highlights those issues to be prioritised in further research. The paper also questions the existing frameworks and methodologies that have been used to study population ageing. Two issues stand out in this regard. Firstly, there is a tendency to view population ageing as a "static" phenomenon. The economic implications of population ageing are pervasive and complex. Future research may benefit from attention to individual behavioural responses to ageing and into the underlying demographic dynamics of population ageing. Secondly, the future economic impacts of an ageing population are inherently uncertain. Future research could well incorporate methodological approaches that attempt to account for these inherent uncertainties.
Keywords: J14; J18; 330; Population Ageing; Economics and Demographic Change